Glycosyl iodides are highly efficient donors under neutral conditions - Hadd, M.J.; Gervay, J.
Glycosyl iodides have been prepared and subjected to glycosylation under neutral conditions. The reactions are highly efficient, giving a glycosides even with sterically demanding glycosyl acceptors. Glucosyl iodides react with allyl alcohol slowest and require refluxing conditions. Galactosyl iodides are intermediate in reactivity, providing the allyl glycoside in 3 h at room temperature, whereas glycosylation of fucosyl iodides occurs in less than 1 h under similar conditions. The scope and limitations of the reactions were demonstrated with a variety of acceptors, including an anomeric hydroxyl group, to give trehalose analogs. b-Selective glycosylation of glucosyl iodides, in the absence of C-2 participation, could be achieved by simply changing the solvent from benzene to acetonitrile.
Keywords: GLYCOSYL IODIDE; GLYCOSYL BROMIDE; A-GLYCOSYLATION; IN SITU ANOMERIZATION; HALIDE-CATALYZED ANOMERIZATION; TREHALOSE ANALOGS